Electrosynthesis of polypyrrole-reinforced helical α-MoO3 microribbons for high-energy aqueous Al3+-ion pseudocapacitors. (10th October 2022) - Elkholy, Ayman E.; Duignan, Timothy T.; Knibbe, Ruth; Zhao, Xiu Song
Highlights: α-MoO3 was modified by electrochemical coating of polypyrrole (PPy). The charge storage properties of samples were studied in 1 M AlCl3 electrolyte. The PPy-coated α-MoO3 shows improved Al 3+ -ion storage and cycling stability. Intercalation pseudocapacitance dominates the charge storage process. Abstract: Orthorhombic molybdenum trioxide (α-MoO3 ) is a promising electrode material for aqueous electrochemical metal-ion storage due to its unique layered structure. However, its poor electronic conductivity and instability in aqueous electrolytes hinder its applications in electrochemical energy storage. In this paper, we report on the electrosynthesis and assessment of electrochemical properties of a polypyrrole-encapsulated α-MoO3 electrode for aqueous Al 3+ -ion storage. This binder-free, PPy-coated α-MoO3 electrode (α-MoO3 @PPy) synthesised using the electrodeposition method has a high mass loading of ∼16 mg/cm 2 . The α-MoO3 @PPy electrode exhibites high cycling stability in 1 M aqueous AlCl3 electrolyte with capacity retention of 88% after 1000 cycles. A full electrochemical Al 3+ -ion pseudocapacitor cell fabricated with the α-MoO3 @PPy as anode and copper hexacyanoferrate (CuHCF) as cathode demonstrates high rate capability delivering energy densities of 0.33 and 0.20 mWh/cm 2 at current densities of 1 and 10 mA/cm 2, respectively. In addition, this cell is stable against cycling with capacity retention of 70% after 1800 cycles. This work provides a straightforward approach to the synthesis of stable α-MoO3 -based electrode materials for aqueous electrochemical energy storage. Graphical abstract: Image, graphical abstract